Gene promoter polymorphism of RUNX2 and risk of osteoporosis in postmenopausal Indonesian women. (13th April 2014) - Auerkari, Elza I; Suryandari, Dwi A; Umami, Sri S; Kusdhany, Lindawati S; Siregar, Tut Wuri A; Rahardjo, Tri Budi W; Talbot, Christopher; Hogervorst, Eef
Objectives: Osteoporosis is a metabolic bone disease of reduced bone mass density (BMD) and elevated risk of fracture due to an imbalance in bone formation and resorption. The risk and incidence of osteoporosis increase towards advanced age, particularly in postmenopausal women, and the risk is known to be affected by the variation in the expression of the associated regulatory genes. This work aimed to clarify the impact of variation in RUNX2 (runt domain transcription factor 2), which is an osteoblast-specific transcription factor that normally stimulates bone formation and osteoblast differentiation, regarding single-nucleotide polymorphism within RUNX2 promoter (P1) and risk of osteoporosis in postmenopausal Indonesian women. Methods: Using DNA sampling from blood, the variation at the single-nucleotide polymorphism (-330, G→T, rs59983488) at the RUNX2 P1 promoter was investigated using polymerase chain reaction–restriction fragment length polymorphism for 180 consenting postmenopausal Indonesian women. The subjects were examined for bone mass density and classification to normal and those with osteopenia or osteoporosis by T-scoring with dual-energy X-ray absorptiometry. Chi-square testing and logistic regression were mainly used for statistical assessment. Results: The results showed a general trend with increased risk of osteoporosis associated with the genotype TT (mutant type) and the corresponding T allele of the tested polymorphism of RUNX2 promoter P1. The trend was, however, not significant in multivariate testing adjusted for age and time after menopause. Conclusion: To confirm the potential risk with TT genotype would require testing of a much larger sample of subjects. As the tested single-nucleotide polymorphism only represents one of the relevant candidate locations of RUNX2, the results are taken nevertheless to suggest an impact by overall RUNX2 variation in the risk of osteoporosis in Indonesian postmenopausal women.